P145 Co-infections due to Aspergillus and Mucorales: Case series from a superspecialty medical center in India. (20th September 2022) - Rana, Bhaskar; Xess, Immaculata; Singh, Gagandeep; Kumar, Rakesh; Soneja, Manish; Jain, Ashima; Choudhury, Ajay Roy
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: To present details of a case series of fungal co-infection (aspergillosis and mucormycosis) including clinical course, laboratory diagnosis, treatment, and outcome. Methods: Clinical histories of 7 cases of fungal co-infection (3 pulmonary, 4 rhino-orbito-cerebral or sino-nasal) were collected by chart review, and reports of samples sent to the mycology laboratory for direct microscopy and fungal culture were retrieved from laboratory records. Presence of septate and aseptate hyphae in direct microscopy of clinical samples and/or growth of Aspergillus spp and Mucorales in culture was considered as evidence of probable co-infection with mucormycosis and aspergillosis (as per EORTC guidelines). Results: Mechanical ventilation, cavitary lung disease, and renal failure with metabolic acidosis were unique risk factors observed for pulmonary co-infection, while use of systemic corticosteroids for treatment of SARS-CoV-2 infection was common in rhino-orbito-cerebral (ROC) or sino-nasal (SN) co-infection. Diabetes mellitus was a common risk factor for both groups of cases. Fever, cough, chest pain, and shortness of breath were the most common features in pulmonary fungal co-infection cases, while headache, facial swelling and pain, nasal stuffiness, decreased vision, and altered sensorium were the most common features in ROC/SN co-infection. Consolidation or collapse, bronciectasis, cavitatory changes in and nodules were the most frequent radiological features in pulmonary fungal co-infection cases, while mucosal thickening in multiple paranasal sinuses, and involvement of orbit and cavernous sinuses were the most frequent features in ROC or SN co-infection. Presence of aseptate and septate hyphae in direct microscopy was seen in tissue samples from all ROC/SN cases, which enabled early intervention. However direct microscopy was not indicative of co-infection in any of sputum samples from pulmonary cases, and diagnosis was only established by culture, leading to delayed initiation of treatment or no treatment. Liposomal amphotericin B (lAMB) ranging from 50-200 mg/day was used for treatment of fungal co-infection, with posaconazole 600-800 mg/day as step-down therapy or if lAMB was not tolerated. Out of three pulmonary fungal co-infection cases, only one received appropriate antifungal treatment but expired nonetheless. Out of the two untreated patients, one expired, and one was discharged against medical advice without resolution of symptoms. Surgical intervention was not done for any patient. In comparison, 3 out of 4 cases of ROC/SN co-infection were appropriately managed with immediate surgical debridement and survived. The remaining patient received appropriate antifungals but refused surgical intervention and expired. Conclusions: Fungal co-infection with aspergillosis and mucormycosis is a serious condition requiring early intervention. This is facilitated by high sensitivity of direct microscopy in tissue samples used for diagnosis in ROC/SN co-infection, but hindered by low sensitivity of direct microscopy in sputum/BAL samples used for diagnosis in pulmonary cases rather than lung biopsy. Robust clinical advisory services, early diagnosis, and combined surgical and pharmacological approaches are crucial to a favorable outcome.